Scientific challenges and biophysical knowledge gaps for implementing nutrient offset projects. (1st August 2023) - Lu, Jing; Burton, Joanne; Garzon-Garcia, Alexandra; Jackson, Cameron; Newham, Michael; Bloesch, Philip; Ramsay, Ian; Rogers, Jenny; Griffith, Merran; Saeck, Emily; Burford, Michele A.
Abstract: Nutrient offsetting allows nutrient point source polluters to pay for diffuse source nutrient reductions, or improvements in nutrient load reductions from alternative point sources. These programs have the potential to provide a more cost-effective approach to achieve water quality goals in waterways compared to infrastructure upgrades. However, worldwide adoption of nutrient offset/trading has not been realized. Here, we identified the biophysical-chemical knowledge gaps that can act as barriers to adopting these programs and summarized areas where further research is needed. This includes a) evaluating if any appropriate spatial scale (local-, catchment-, or regional-scale) and time scale (especially for areas with dry/wet cycles) exists to achieve nutrient load management goals, and b) quantifying nutrient characteristic differences and load contributions between point and diffuse sources to determine possible offsets between the two. Where offsets are appropriate, there is also a need to 1) improve monitoring design and reduce modelling uncertainties to better quantify diffuse nutrient loads; 2) quantify and manage uncertainties in catchment interventions to reduce nutrient loads, and design effective long-term monitoring and maintenance to sustain intervention outcomes; 3) prioritize areas within catchments that are key nutrient sources for catchment interventions to achieve the optimal outcomes for nutrient load management and catchment and aquatic ecosystem health; and 4) develop methodologies to determine the environmental equivalency ratio between different nutrient sources in terms of ecosystem effects. This would include identifying the best metric to quantify equivalency ratios, determining discharge patterns for different nutrient sources, and linking this with ecosystem responses across seasons and in the downstream receiving environment. Addressing the identified knowledge gaps will improve the program feasibility assessment process as well as confidence and certainty in the environmental outcomes of nutrient offsetting. Highlights: Biophysical knowledge gaps were identified for nutrient offset from literature. Key strategies to address knowledge gaps were provided in the review. Key strategies suggested can improve offset project feasibility assessments. Key strategies can increase confidence in environmental outcomes of nutrient offset.